Reproductive performance of sows after reducing litter size for five days before weaning - Stevenson, Jeffrey S.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our objective was to characterize reproductive performance for sows nursed by only two to four pigs for the last 5 days of lactation. Litter size was reduced beginning at 2 (16 sows), 3 (15 sows), or 4 (15 sows) weeks after farrowing, while 14 sows had no change in their litter size and were weaned at 5 weeks. Reducing litter size (RLS) resulted in 19 of 46 (41 %) sows showing estrus at weaning. More (P<.05) RLS sows were in heat 0 to 3 days after weaning compared with control sows. Fertility traits (number of corpora lutea, eggs fertilized, fertilization rate, cleaved eggs, and cleavage rate) were determined 4 to 6 days after estrus and were unaffected by treatment. Intervals to estrus after weaning were reduced using the RLS treatment while maintaining normal fertility after inseminations at the early estrus. However, for those sows not in heat at weaning in response to RLS treatment, intervals to estrus were less synchronous than for controls.
Keywords: Swine; Reproductive; Performance; Sows